ANALISA PERANCANGAN SISTEM INFORMASI MONITORING QUALITY AGENT SOCIAL MEDIA BERBASIS WEBSITE - Delaila Rosa Wardiman; Bagus Priambodo (Ensiklopedia of Journal, 2019)
PT. XYZ had 199 social media agents, 16 Team Leaders, 15 Quality Control Teams. All agents are sued for provide the right information and provide good services to customers for 24 hours. Quality teams was formed to monitor service quality for customers. Monitoring is carried out every day, and the result of monitoring will be given every 10 days (one period) from Quality Control Teams through Team Leaders. at this time, the result of monitoring are recapitulated manually using Microsoft Excel and sent via email. the result of monitoring will be seen by Team Leaders, if there is incompatibility then carried out the justifications process by email. currently monitoring process and justifications are carried out manually. The purpose of this research is to simplify monitoring process and make the process of monitoring more well- documented. This research using SWOT Analysis and Fishbone Diagram which called as Cause and Effect Diagram in analyzing related problems that experienced at this time, and produce solutions as expected. SWOT Analysis is abbreviation from internal environment which Strengths and Weakness, and external environments which Opportunities and Threats